Designing tools for context-aware adaptive mobile learning - Zervas, P.; Ardila, S.; Fabregat, R.; Sampson, Demetrios (2011)
During the past years, ubiquitous computing has influenced Technology-enhanced Learning. This is widely known as ubiquitous learning. On the other hand, the widespread ownership of mobile devices has lead to an increased interest to ubiquitous learning that is supported by mobile devices. This is commonly referred to as mobile learning. An important success factor for ubiquitous and mobile learning is the pedagogically meaningful and technically feasible process of learners' contextual information. While the formal definition of context is still an open issue, contextual information in Technology-enhanced Learning involves information that characterizes a learners' given situation. Thus, in order to achieve personalized and ubiquitous learning, tools for context-aware adaptive learning designs (authoring tools) and context-aware adaptive delivery of learning activities (run-time tools) are needed. In this paper, we target addressing this issue, that is, we describe a set of tools that incorporate a context-aware content adaptation mechanism at both the learning design and mobile delivery process.